PENGARUH PERSEPSI MUTU PROSES PEMBELAJARAN KELAS TERHADAP KEPUASAN MAHASISWA DI PROGRAM STUDI DIII KEBIDANAN STIKES WIDYA HUSADA SEMARANG TAHUN 2012 - Ambar Dwi Erawati, Sri Wahyunin, Rinayati, (Jurnal Ilmu dan Teknologi Kesehatan, 2012)
EFFECT OF PERCEPTION OF LEARNING PROCESS QUALITY CLASS STUDENT SATISFACTION STUDY IN MIDWIFERY STIKES DIII WIDYA HUSADA Semarang IN 2012Education Diploma in Midwifery education oriented to the development of science and echnology as well as professional development and drafting institute the core competence of midwives in Indonesia. Based on these competencies it is expected that graduates of midwifery diploma mastered science, technology, skills and attitudes and behavior of professional midwives. To be able to produce a midwife who has competence in accordance with the expected then it takes the management of quality education. Management of providing quality education to the students satisfaction. This research is observational analytic survey method through cross-sectional approach. Data collection was conducted by questionnaire using a structured questionnaire. The population is all 4                               J. Ilmu dan Tek. Kesehatan (JITK), Vol. 3 No. 1     Januari 2012: 30-37 students D3 Midwifery STIKES Widya Husada (320) sampling with non proportionale random sampling technique. (178). Univariate analysis using frequency distribution, bivariate analysis using cross tabulations, chi square while multivariate analysis using multiple logistic regression. The results showed most respondents have a perception of the quality of the learning process dimension of reliability (57.86%), responsiveness (50%), certainty (67.41%), empathy (50.56) either. But in terms of the dimensions of the form (55.05%) said that good, student satisfaction (60.11%) either. Bivariate analysis showed a significant relationship between reliability (p = 0.001), responsiveness (p = 0.001), certainty (p = 0.006), empathy (p = 0.002), being (p = 0.0001) with student satisfaction. Multivariate results show that the perception of the quality dimensions of a form that has the most impact on satisfaction mahasiswa.Direkomendasikan at Widya STIKES Husada to improve the quality of the learning process of the five aspects of quality dimensions, especially in the aspects of physical form. be spacious room, cleanliness, completeness laboratory equipment, neatness classrooms and laboratories, and the coolness of the room. Keywords: student satisfaction, the learning process, the quality of learning